An Annotated Checklist of the Taxonomic and Conservation Status of Land Mammals in the Philippines - Heaney, Lawrence R.; Gonzales, Pedro C.; Alcala, Angel C. (Silliman Journal, 2024)
The mammal fauna of the Philippine Islands is currently considered to contain 165 species in the following orders (with number of species) : Insectivora (10); Scandentia (2); Dermoptera (1); Chiroptera (69); Primates (3); Pholidota (1); Rodentia (66); Carnivora (7); Artiodactyla (6). We summarize information on the distribution, taxonomic. and conservatory status of each species, and provide a brief summary and bibliography of literature on Philippine animals.